Assessment of body composition in adolescents with obesity undergoing avocado oil supplementation - Aline Peres Leite Filizzola; Clara Korukian Freiberg; Priscila Sala Kobal; Sandra Maria Chemin Seabra da Silva; Adriana Garcia Peloggia de Castro; Deborah Cristina Landi Masquio; Yasmin Hany Saied; José Osmar Cardoso Filho; Aline de Piano Ganen (O Mundo da Saúde)
The prevalence of obesity is considered a global epidemic, with severe repercussions for public health. Therefore, the objective is to present preliminary data on the application of avocado oil as a supplement for the treatment of obesity. A randomized, double-blind, placebo-controlled clinical trial was conducted at a school clinic in the municipality of São Paulo. Thirty post-pubertal adolescents aged between 12 and 19 years were selected. They were divided into: group A (n=09), supplemented with 4 capsules/day containing 500 mg of avocado oil = 2 g of avocado oil; group B (n=12), supplemented with 2 capsules/day containing 500 mg of avocado oil = 1 g of avocado oil; and group C (n=09), supplemented with 2 capsules/day containing 500 mg of mineral oil – placebo group = 1 g of mineral oil. Anthropometric measurements such as body mass, height, body mass index (BMI), waist circumference (WC), neck circumference (NC), blood pressure, body composition by bioimpedance (Biodynamics), and ultrasound (Body Metrix) were evaluated. A significant increase in body mass was observed in the group supplemented with 1g, as well as a reduction in resistance, extracellular mass (kg), BMR, intracellular water (L), total water (L), FFM lean mass, and FFM total weight. The placebo group showed a reduction in resistance, an increase in body cell mass, lean mass, BMR, intracellular water (L), FFM lean mass, and FFM total weight. It was concluded that, despite the ingestion of a bioactive compound aiding in obesity control, qualitative changes related to eating habits remain crucial for achieving significant results in body composition.